AKTUALISASI BAHASA SASTRA ALAM PENDIDIKAN KARAKTER - Al-Ma’ruf, Ali Imron; Nugrahani, Farida (Prosiding Seminar Nasional dan Internasional HISKI, 2024)
The objective is to: (1) describes the relevance of literature language to the nation's character, (2) describe the contribution of literature language in character education of the nation. The study used descriptive qualitative method with inductive logic. The object of this research is literature language as an alternative to character education in the nation. The research data in the form of soft data that is words, phrases, sentences, and discourse that contain elements of character education in Indonesian literature. Data collected with libraries technique, see and record. Data analysis was performed with contens methods of analysis and reading of the semiotic model which consists of reading heuristics and hermeneutics. The results of this study are: (1) literature with a variety of genre has a strong relevance to the human character, (2) works of literature language have an important contribution in the nation of character education. Literature can be used as an alternative in a nation of character education. Through the appreciation of literature, the reader will be able to find the moral values and ideas about human existence that are useful to enrich the human mind. Moral values, among others: the willingness to accept the guilty, the importance of the struggle of life, humanity and social sensitivity, moral in the art, the importance of morals in life, religion and religiosity, willingness to accept differences, and gender perspectives.